Reducing the risk of air pollution in working areas by construction dust using a combined dust collector - Vasiutynska, Kateryna; Karamushko, Anzhelika; Butenko, Oleksandr; Surkov, Sergii; Melnyk, Serhii (Technology audit and production reserves, 2025)
The object of research is methods for reducing the level of air pollution in working areas with industrial dust. The problem of reducing the impact of dustiness of production premises on the workers' health is solved by improving the aspiration air purification system. A new approach is proposed that provides the blower (fan) with an additional purification function by attaching a dust collector to its housing. By organizing the circulation movement of the dust-gas flow, part of the dust settles in the dust collector before it enters the main dust collector. Such a combined dust collector can be used as an independent device in closed aspiration systems or as part of complex dust removal systems, reducing the load on the main device. A methodology for calculating purification indicators has been developed, which is based on the discretization of the differential dust mass distribution curve by particle size. The method allows to assess the efficiency of the process, determine the dimensions of the dust collection container and the frequency of dust discharge from it. The technology was used for the air aspiration system of the working area of the building materials processing facility to reduce the risk to workers' health from air pollution. The calculations have established the conditions of acceptable non-carcinogenic risk at the level of construction dust concentration not higher than 61.42 mg/m3, and with the introduction of the proposed combined dust collector, it is possible to increase the dust level to 99.1 mg/m³ without exceeding the risk threshold. The proposed technology is cost-effective, requires minimal design changes and can be implemented at most industrial facilities, especially in conditions of high dustiness of production premises.